The reaction against realism in contemporary American fiction: a study of the work of John Hawkes, John Barth and Thomas Pynchon - Mackenzie, Ursula A. (1978)
This thesis explores the reaction against realism in the work of three contemporary American novelists, John Barth, John Hawkes and Thomas Pynchon, with a view both to elucidating their individual literary styles and concerns, and to suggesting why these writers no longer consider realism a valid fictional mode.